Fernwärme klimaneutral transformieren. Eine Bewertung der Handlungsoptionen am Beispiel Berlin Nord-Neukölln. - Dunkelberg, Elisa; Deisböck, Alexander; Herrmann, Benjamin; Hirschl, Bernd; Mitzinger, Tino; Röder, Johannes; Salecki, Steven; Thier, Pablo; Wassermann, Timo (My University, 2020)
Fernwärme ist in Berlin wie in vielen anderen Großstädten wichtiger Bestandteil der urbanen Wärmeversorgung – etwa 40 % der Wohnungen beziehen in der Hauptstadt Fernwärme. Da in der Fernwärme überwiegend fossile Energieträger eingesetzt werden, muss die Fernwärmeerzeugung eine Transformation durchlaufen, um dem Klimaschutz- und Kohleausstiegsziel des Landes Berlin gerecht zu werden. Die Studie zeigt basierend auf Analysen zur Entwicklung des Wärmebedarfs und zu den Potenzialen an erneuerbarer Wärme und Abwärme im Versorgungsgebiet Nord-Neukölln unterschiedliche Erzeugungsoptionen für die dortige Fernwärme auf.

District heating in Berlin, like in many other cities, makes a significant contribution to the heat sup-ply – in the capital of Germany, 40% of the apartments use district heating. Since fossil fuels are predominantly used as an energy source in district heating, district heating has to undergo a trans-formation in order to meet the climate protection and coal phase-out goals of the state of Berlin. Based on analysis of the development of heat demand and the potential of renewable heat and waste heat in the North of Neukölln, the study shows different generation options for the district heating there. A transformation path for district heating can be derived from the heat generation costs and CO2eq emissions. The first phase focuses on the coal phase-out, the expansion of gas-based CHP and PtH, the integration of waste heat and the implementation of pilot plants for the integration of wastewater and river water heat as well as deep geothermal energy.
Keywords: Fernwärme; Fernwärmeerzeugung; CO2-Emission; Emissionsbelastung; Fossiler Brennstoff; Wärmebedarf; Bedarfsprognose; Szenario; Energetische Sanierung; Erneuerbare Energie; Ökologische Erneuerung; Klimaschutz